2019
DOI: 10.3390/buildings9060150
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Demolition Waste Management Actions and Potential Benefits: A Perspective from Trinidad and Tobago

Abstract: A study was conducted to identify the primary sources and types of construction and demolition (C&D) waste, determine current and potential management actions which can be applied to the respective wastes, and assess the potential benefits, barriers, and recommendations towards the implementation of a C&D waste management plan in Trinidad and Tobago-a Caribbean Small Island Developing State (SIDS). This process is lacking locally, and will benefit decision makers and other stakeholders in proper management of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 15 publications
1
7
0
3
Order By: Relevance
“…Tabela 2 -Barreiras técnicas que impedem a redução de RCC Barreiras Referências Falta de projeto executivo bem elaborado e compatibilizado (Giorgi et al, 2022); (Condotta & Zatta, 2021) ; (Negash et al, 2021); (Spišáková et al, 2021) ; (Olanrewaju & Ogunmakinde, 2020); (Pellegrini et al, 2020) ; (Low et al, 2020); (Mawed et al, 2020); (Vidyasekar & Selvan, 2019) ; (Liyanage et al, 2019); (Narcis et al, 2019) ; (Mahpour, 2018); (Udawatta et al, 2018); (Ling & Nguyen, 2013) ; (de Souza Campos et al, 2013) 15 Alterações de projeto por parte do cliente (Spišáková et al, 2021) ; (Olanrewaju & Ogunmakinde, 2020) ; (Pellegrini et al, 2020) ; (Mawed et al, 2020) ; (Liyanage et al, 2019); (Narcis et al, 2019) 6 Inadequada descarga de material (Olanrewaju & Ogunmakinde, 2020) ; (Low et al, 2020); (Mawed et al, 2020); (Liyanage et al, 2019) ; (Narcis et al, 2019) 5 Armazenamento não adequado de materiais. (Olanrewaju & Ogunmakinde, 2020) ; (Mawed et al, 2020) ; (Narcis et al, 2019) 3 Falta de qualidade dos materiais de construção (Spišáková et al, 2021) ; (Olanrewaju & Ogunmakinde, 2020) ; (Low et al, 2020); (Ratnasabapathy et al, 2021) ; (Mawed et al, 2020); (Liyanage et al, 2019) ; (Narcis et al, 2019) ; <...…”
Section: Resultados E Discussõesunclassified
See 2 more Smart Citations
“…Tabela 2 -Barreiras técnicas que impedem a redução de RCC Barreiras Referências Falta de projeto executivo bem elaborado e compatibilizado (Giorgi et al, 2022); (Condotta & Zatta, 2021) ; (Negash et al, 2021); (Spišáková et al, 2021) ; (Olanrewaju & Ogunmakinde, 2020); (Pellegrini et al, 2020) ; (Low et al, 2020); (Mawed et al, 2020); (Vidyasekar & Selvan, 2019) ; (Liyanage et al, 2019); (Narcis et al, 2019) ; (Mahpour, 2018); (Udawatta et al, 2018); (Ling & Nguyen, 2013) ; (de Souza Campos et al, 2013) 15 Alterações de projeto por parte do cliente (Spišáková et al, 2021) ; (Olanrewaju & Ogunmakinde, 2020) ; (Pellegrini et al, 2020) ; (Mawed et al, 2020) ; (Liyanage et al, 2019); (Narcis et al, 2019) 6 Inadequada descarga de material (Olanrewaju & Ogunmakinde, 2020) ; (Low et al, 2020); (Mawed et al, 2020); (Liyanage et al, 2019) ; (Narcis et al, 2019) 5 Armazenamento não adequado de materiais. (Olanrewaju & Ogunmakinde, 2020) ; (Mawed et al, 2020) ; (Narcis et al, 2019) 3 Falta de qualidade dos materiais de construção (Spišáková et al, 2021) ; (Olanrewaju & Ogunmakinde, 2020) ; (Low et al, 2020); (Ratnasabapathy et al, 2021) ; (Mawed et al, 2020); (Liyanage et al, 2019) ; (Narcis et al, 2019) ; <...…”
Section: Resultados E Discussõesunclassified
“…Alterações climáticas (Mawed et al, 2020); (Narcis et al, 2019) 2 Fonte: Autores Falta de projeto executivo bem elaborado e compatibilizado refere-se à ausência de um projeto executivo, com todos os elementos e detalhes necessários para a execução, em que deve conter todas as informações suficientes para o cumprimento em todas as etapas da obra, em conformidade com as normas da Associação Brasileira de Normas Técnicas (ABNT), de acordo com a Lei 8.666 de 21 de junho de 1993 (Brasil, 1993) Tabela 3 -Barreiras econômicas que impedem a redução de RCC Barreiras Referências Falta de recurso financeiro (Negash et al, 2021) ; (Spišáková et al, 2021) ; (Olanrewaju & Ogunmakinde, 2020); (Bailey et al, 2020); (Ratnasabapathy et al, 2021); (Mawed et al, 2020); (Ling & Nguyen, 2013) ; (de Souza Campos et al, 2013) 8 Falta de retorno econômico com a reciclagem dos RCC (Giorgi et al, 2022) ; (Yu et al, 2021); (Condotta & Zatta, 2021) ; (Negash et al, 2021) ; (Diotti et al, 2021) ; (Bao et al, 2020); (Spišáková et al, 2021) ; (Olanrewaju & Ogunmakinde, 2020) ; (Low et al, 2020); (Bailey et al, 2020); (Ratnasabapathy et al, 2021) ; (Mawed et al, 2020) ; (Liyanage et al, 2019) ; (Mahpour, 2018); (Udawatta et al, 2018) ; (Owolana & Booth, 2016) 16 Custo de implantação de novas tecnologias que diminuem os RCC (Gagnon et al, 2022) ; (Giorgi et al, 2022) ; (Yu et al, 2021); ; (Condotta & Zatta, 2021) ; (Diotti et al, 2021) ; (Bao et al, 2020); (Spišáková et al, 202...…”
Section: Resultados E Discussõesunclassified
See 1 more Smart Citation
“…From an economic perspective, the construction sector is a significant contributor towards employability by absorbing a bigger chunk of the labor force. On the other hand, construction projects are intrinsically irresponsible towards the environment and the community [32] as they involve extensive use of materials and energy. This significantly contributes to environmental degradation and disturbs the ecosystem [33].…”
Section: Sustainable Project Managementmentioning
confidence: 99%
“…In addition to the concern during the planning and execution of construction works as to energy consumption, another important concern is with the waste material generated and with demolition [29,30]. Ding, Wang and Zou [31] showed that about 30 to 40% of the waste generated in China comes from construction and demolition and that this waste needs to be managed.…”
Section: Sustainability In Civil Constructionmentioning
confidence: 99%